Effect of the specimen volume of chemosetting polyester resin on the curing process - Kozioł, M.; Mocek, P.; Jankowski, P. (Polimery, 2021)
The paper presents an experimental evaluation of the influence of polyester resin specimen volume on the time and temperature of curing process. It was found that the maximum peak temperature increased with an increase of the resin volume up to 120 cm³ (Figs. 4—6) while the curing time was decreased. The stiffness of the resin cured with the use of a more active initiator decreased with an increase in the resin volume and increased when a less active initiator was employed (Figs. 9 and 10). The mathematical modelling of the thermodynamics of curing process was performed using a model of distributed parameters system, describing the chemically determined curing process with heat diffusion. A strong influence of convective cooling on the course of the process was found.